Fermentative Production of l-2-Hydroxyglutarate by Engineered Corynebacterium glutamicum via Pathway Extension of l-Lysine Biosynthesis - Prell, Carina; Burgardt, Arthur; Meyer, Florian; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2021)
ʟ-2-hydroxyglutarate (ʟ-2HG) is a trifunctional building block and highly attractive for the chemical and pharmaceutical industries. The natural ʟ-lysine biosynthesis pathway of the amino acid producer Corynebacterium glutamicum was extended for the fermentative production of ʟ-2HG. Since ʟ-2HG is not native to the metabolism of C. glutamicum metabolic engineering of a genome-streamlined ʟ-lysine overproducing strain was required to enable the conversion of ʟ-lysine to ʟ-2HG in a six-step synthetic pathway. To this end, ʟ-lysine decarboxylase was cascaded with two transamination reactions, two NAD(P)-dependent oxidation reactions and the terminal 2-oxoglutarate-dependent glutarate hydroxylase. Of three sources for glutarate hydroxylase the metalloenzyme CsiD from Pseudomonas putida supported ʟ-2HG production to the highest titers. Genetic experiments suggested a role of succinate exporter SucE for export of ʟ-2HG and improving expression of its gene by chromosomal exchange of its native promoter improved ʟ-2HG production. The availability of Fe2+ as cofactor of CsiD was identified as a major bottleneck in the conversion of glutarate to ʟ-2HG. As consequence of strain engineering and media adaptation product titers of 34 ± 0mM were obtained in a microcultivation system. The glucose-based process was stable in 2 L bioreactor cultivations and a ʟ-2HG titer of 3.5 g L-1 was obtained at the higher of two tested aeration levels. Production of ʟ-2HG from a sidestream of the starch industry as renewable substrate was demonstrated. To the best of our knowledge, this study is the first description of fermentative production of ʟ-2HG, a monomeric precursor used in electrochromic polyamides, to cross-link polyamides or to increase their biodegradability.